The Impact of Country of Origin, Image, and Consumer Ethnocentrism Toward Purchase Decision of Casual Apparel in Young Adult - Alyssa Chairiena; Leonnard Ong; Liza Agustina Maureen Nelloh (International Journal of Business Studies, 2022)
Indonesia is among the top 10 textile and apparel producer in the world the industry has become more competitive in both domestic and international markets. Indonesian Government has also been making tremendous effort in boosting local product purchases with the aim of making domestic consumption as the main pillar of Indonesian economy. However, data and statistic still shown the lack of appreciation from Indonesian consumers toward its apparel industry. The purpose of this study is to examine the impact of Country of Origin Image and Consumer Ethnocentrism toward Purchase Decision of casual apparel in young adult. The data used was primary data which was obtained through self- administered questionnaire and processed quantitatively using multiple regression in SPSS to test the hypotheses exploring the impact Country of Origin Image and Consumer Ethnocentrism toward Purchase Intention. A total sample of 100 respondents were collected. The result showed that Country of Origin Image does not have significant impact toward Purchase Decision. In contrast, Consumer Ethnocentrism does have significant impact toward Purchase Decision. The result of this study further supports and add to previous research of Country of Origin Image and Consumer Ethnocentrism concepts together. Moreover, the result of this study can benefit Indonesian casual apparel companies in providing additional insights which can further support and add to their existing sales and marketing strategies to maximize their competitive force in local market.